An Entropy Measure of Emotional Arousal via Skin Conductance Response (Journal of Fiber Bioengineering and Informatics, 2014)
Whether different affective states have specific physiological activation patterns still does not have anexact interpretation and clear validation. Skin Conductance Response (SCR) is under strict control ofthe autonomic nervous system, providing an efficient way to measure the emotional reactions. Since theemotional SCR signals are always short and noisy, it is of great value to study the methods suitablefor short-term SCR analysis. According to the characteristic of SCR signal, we proposed a symbolicmethod and the symbolic information entropy, further, applied the method to analyse emotional SCRsignals. Experiment results show that the symbolic information entropy of SCR is in accordance withthe arousal level of emotions, and SCR is more sensitive to the variations of emotional arousal ratherthan to valence. Symbolic information entropy is less influenced by noise and non-stationary, providingan effective method in analyzing SCR signals or other complex physiological signals.